2012
DOI: 10.1152/japplphysiol.00925.2011
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of muscle deoxygenation and microvascular Po2 during contractions in rat: comparison of optical spectroscopy and phosphorescence-quenching techniques

Abstract: The overarching presumption with near-infrared spectroscopy measurement of muscle deoxygenation is that the signal reflects predominantly the intramuscular microcirculatory compartment rather than intramyocyte myoglobin (Mb). To test this hypothesis, we compared the kinetics profile of muscle deoxygenation using visible light spectroscopy (suitable for the superficial fiber layers) with that for microvascular O(2) partial pressure (i.e., Pmv(O(2)), phosphorescence quenching) within the same muscle region (0.5∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 59 publications
3
54
0
Order By: Relevance
“…In the present study, we did observe a significant association between a decreased G p with the relative speeding of the MRT‐Δdeoxy[Hb+Mb] following the onset of U → VH compared to U → M. It has been reported that the τ of deoxy[Hb+Mb] kinetics coheres with that observed for the reduction in microvascular PnormalO2 following the onset of skeletal muscle contractions (Koga et al., ). Accordingly, it is conceivable that those participants evincing a greater Q̇normalO2‐to‐V̇normalO2 mismatch (i.e.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we did observe a significant association between a decreased G p with the relative speeding of the MRT‐Δdeoxy[Hb+Mb] following the onset of U → VH compared to U → M. It has been reported that the τ of deoxy[Hb+Mb] kinetics coheres with that observed for the reduction in microvascular PnormalO2 following the onset of skeletal muscle contractions (Koga et al., ). Accordingly, it is conceivable that those participants evincing a greater Q̇normalO2‐to‐V̇normalO2 mismatch (i.e.…”
Section: Discussionsupporting
confidence: 85%
“…A caveat particularly pertinent to the present study, however, is its inability to differentiate Hb from Mb with regard to light absorption. However, by comparing muscle deoxygenation with PO 2mv , determined by phosphorescence quenching within the same muscle region in rat preparations, Koga et al (29) confirmed that the deoxygenation signal did provide a valid index of local fractional O 2 extraction kinetics during exercise transients.…”
Section: Discussionmentioning
confidence: 99%
“…Barstow, ). In particular, time‐resolved NIRS (TR‐NIRS) was used to investigate non‐invasively the trueQ̇O2normaltotrueV̇O2 matching {via deoxy[haemoglobin + myoglobin] (deoxy[Hb + Mb]) and tissue O 2 saturation (SnormaltO2)} and microvascular haematocrit (via total[Hb + Mb]) within specific muscle regions (Federspiel & Popel, ; Groebe & Thews, ; Koga et al., , ; Okushima et al., ). Crucially, TR‐NIRS measures in vivo optical path length distribution, facilitating resolution of absolute [Hb + Mb].…”
Section: Introductionmentioning
confidence: 99%